Effects of dietary fat type and energy restriction on adipose tissue fatty acid composition and leptin production in rats - Geoffrey R. Hynes; Jode Heshka; Kris Chadee; Peter J. Jones (Journal of Lipid Research, 2003)
To investigate whether dietary fatty acid (FA) composition and energy restriction (ER) interactively influence obese (ob) gene expression, rats consumed diets containing beef tallow, safflower, or fish oil ad libitum (AL) or at 60% AL intake. Circulating leptin concentrations were higher (P < 0.0001) after AL feeding, but were not influenced by dietary fat. ER decreased (P < 0.0001) weight gain and visceral adipose weight, which were positively correlated (r = 0.40 P < 0.001, r = 0.58 P < 0.0001) with circulating leptin levels. Visceral adipose ob mRNA levels were greater in animals fed unsaturated fats, particularly safflower oil, which had the highest ob mRNA levels. Circulating leptin levels did not parallel ob mRNA levels, except for the greater abundance detected in AL adipose in comparison to ER animals. In addition, visceral FA profiles reflected dietary fat source and were influenced by an interaction of dietary fat and energy. These data demonstrate that dietary fat, particularly from a plant or marine source, and ER interactively influence ob mRNA levels; however, alterations in ob mRNA do not confer changes in circulating leptin, with the exception of ER, which is a key determinant.Thus, dietary intake is an important regulator of leptin production; however, the significance of these modest changes in diet-induced obese animals requires further study.